The Need and Use of Geographic Information Systems for Environmental Impact Assessment in Nepal (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Geographical applications in EIA studies is appropriate to build up and extend their knowledge and skills in using Geographic Information Systems (GIS) in Environmental Impact Assessments (EIA), and obtain practical experience in the application of GIS technologies and disciplines. This article highlights emerging topics related to the principles and practice of EIA, including concepts, tools and methods, and related issues. GIS as a tool will be used to visually illustrate the implications of spatial decisions. GIS is applied in all EIA stages: from the acquisition, storage and display of thematic information relative to the vulnerability of the affected resources, to impact prediction and qualification, evaluation, and finally, presentation. This paper highlights how GIS applications using in EIA process in different countries and find out possibility to incorporate those applications in EIA studies in Nepal.Hydro Nepal: Journal of  Water, Energy and Environment, Issue 4 2009 pp.21-23